Flows and waste reduction strategies of PE, PP, and PET plastics under plastic limit order in China - Chu, Jianwen; Zhou, Ya; Cai, Yanpeng; Wang, Xuan; Li, Chunhui; Liu, Qiang (Resources, conservation and recycling, 2023)
•The flow model and framework for PE, PP, and PET plastics are established.•The waste amount of PET was the largest, followed by PE waste.•Untreated waste cannot be ignored, and its proportion exceeded that of incineration.•Under the scenario of multiple measures, the total waste will reduce by 69.12 Tg. Plastic pollution is a global threat. China's plastic limit order has the most significant impact on plastic pollution. However, under the plastic limit order, the change characteristics of flows and waste for polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) (the most widely used plastics in China) are unknown. Therefore, this study explored the flow characteristics of PE, PP, and PET based on material flow analysis, then considered the impact of the plastic limit order on them, and obtained the most effective strategies for mitigating plastic pollution. The study found that if plastic waste is not controlled, the total amount will reach 128.84 Tg, an increase of 116% over 2017. The PET waste was the largest, followed by PE waste. Moreover, the waste reduction under multiple strategies would be the most significant, and the waste of PE, PP, and PET would reduce by 23.32, 16.84, and 28.96 Tg respectively, and the total would reduce by 69.12 Tg, 54% less than the “business as usual (BAU)” in 2030. The second is the alternative strategies, which is 33% less than BAU (reducing by 42.11 Tg), followed by strategies of prohibition (reducing by 24.29 Tg) and standardizing waste management. Notably, PE waste from packaging and agriculture is reduced most significantly under the prohibition strategy. This study expounds on the reduction potential and strategies of PE, PP, and PET waste under plastic limit order, which will provide a scientific basis for promoting the sustainable consumption of plastics and realizing the waste reduction goal.